The Vulcan Version 3.0 High‐Resolution Fossil Fuel CO2 Emissions for the United States. Issue 19 (5th October 2020) - Gurney, Kevin R.; Liang, Jianming; Patarasuk, Risa; Song, Yang; Huang, Jianhua; Roest, Geoffrey
Abstract: Estimates of high‐resolution greenhouse gas (GHG) emissions have become a critical component of climate change research and an aid to decision makers considering GHG mitigation opportunities. The "Vulcan Project" is an effort to estimate bottom‐up carbon dioxide emissions from fossil fuel combustion and cement production (FFCO2 ) for the U.S. landscape at space and time scales that satisfy both scientific and policy needs. Here, we report on the Vulcan version 3.0 which quantifies emissions at a resolution of 1 km 2 /hr for the 2010–2015 time period. We estimate 2011 FFCO2 emissions of 1, 589.9 TgC with a 95% confidence interval of 1, 367/1, 853 TgC (−14.0%/+16.6%), implying a one‐sigma uncertainty of ±8%. Per capita emissions are larger in states dominated by electricity production and industrial activity and smaller where onroad and building emissions dominate. The U.S. FFCO2 emissions center of mass (CoM) is located in the state of Missouri with mean seasonality that moves on a near‐elliptical NE/SW path. Comparison to ODIAC, a global gridded FFCO2 emissions estimate, shows large total emissions differences (100.4 TgC for year 2011), a spatial correlation of 0.68 (R 2 ), and a mean absolute relative difference at the 1 km 2 scale of 104.3%. The Vulcan data product offers a high‐resolution estimate of FFCO2 emissions in every U.S. city, obviating costly development of self‐reported urban inventories. The Vulcan v3.0 annual gridded emissions data product can be downloaded from the Oak Ridge National Laboratory Distributed Active Archive Center (Gurney, Liang, et al., 2019, https://doi.org/10.3334/ORNLDAAC/1741 ). Plain Language Summary: The emission of greenhouse gases into the Earth atmosphere is driving climate change. The largest single emission category is the release of carbon dioxide from the combustion of fossil fuels. Cities account for roughly 70% of the global emissions of fossil fuel carbon dioxide. Understanding where and when these emissions occur is critical to the science of climate change and to guiding the steps needed to lower these emissions. The Vulcan version 3.0 fossil fuel carbon dioxide emissions data product quantifies all of these emissions for the entire U.S. domain at spatial scales of 1 km 2 for every hour from the years 2010–2015. It is constructed from a large number of publicly available data sources such as pollution reporting, energy statistics, powerplant stack monitoring, and traffic counts. This data product is freely available for scientific research and policy guidance purposes and offers insights, understanding, and application to practical questions. Key Points: Vulcan v3.0 is the first U.S.‐wide bottom‐up FFCO2 emissions data product at 1 km 2 /hourly for multiple years Comparison to satellite‐driven global FFCO2 emissions shows large spatial differences with a mean gridcell absolute relative difference of 104.3% Vulcan can provide an immediate Scope 1 FFCO2 inventory for every city in the United States saving city time and resources